Scientific production of Peruvian universities on health topics during 2014 and 2015 - Moquillaza Alcántara, Victor Hugo (2018)
The university scientific production at the Latin-American level is still far below the international level. In spite of this, there are no publications describing this situation in Peru. Therefore, it was sought to determine the scientific production on health topics in indexed and non-indexed journals during the years 2014 and 2015 through an analysis of the secondary database of the National Council for Science, Technology and Technological Innovation (CONCYTEC). It was found that the median ranged between 1 and 2 articles published by university per year, with the production increasing between 10 and 98,16 % in national indexed and non-indexed journals, and decreasing in 42,86 % in international non-indexed journals.